Chromophobe renal cell carcinoma, oncocytic variant: Cytological and ultrastructural observations - Tadanori Yamaguchi (Journal of Cytology, 2015)
There is only one report on cytological findings of oncocytic variant of chromophobe renal cell carcinoma (RCC). In this article, we report a new case with focus on cytological, and ultrastructural findings. A 60-year-old Japanese man was found to have a right renal tumor on medical checkup. In imprint cytological materials, the smears consisted of slightly discohesive clusters and isolated tumor cells with granular green colored cytoplasm on Papanicolaou staining. Nuclei were generally round and centrally located in the cytoplasm, but nuclear irregularity or perinuclear halo was absent. Ultrastructurally, the tumor was full of mitochondria with tubulovesicular cristae. Fluorescence in situ hybridization study using histological material showed multiple chromosomal losses including chromosomes 7, 10, 13, and 17. This finding supports the hypothesis that this variant may ultrastructurally show the nature of chromophobe RCC rather than renal oncocytoma.